The Problems faced by the Displaced Women Community and its effect on Gender Equality - Selvarajan, P. (Royal Asiatic Society and Open University of Sri Lanka., 2010)
This research study mainly focuses on understanding how far the gender equality has been maintained in our society after the displacements, the problems encountered by the displaced women and finding the ways and means to reduce the gender based violence among them, since there is a necessity to implement it all over the island. During the war in the Wanni region, a huge displacement took place and several civilians were killed and handicapped. This paper also reveals the difficulties and the problems of women after the displacement; Changing pattern of their life style, perception, attitudes, personality and behavior and how did these changes affect the gender equality in various places such as at home, working place and society. This study was conducted among the 100 women internally displaced people (IDPs) who were residing at various welfare centers in Vavuniya during the post war period. A judgment sampling and personal interviewing methods were adopted to collect the information accurately and correctly. Findings showed that there were several forms of problems faced by women community in various places. The discrimination of women, neglecting their rights, lack of basic facilities (health and sanitation) absence of psychosocial care and gender based violence have been identified as major obstacles for their development. It is recommended that proper rehabilitation programs should be organized by respecting the feelings and preferences of IDPs; the resettlement process to be fastened and coordinating with the appropriate organizations to ensure the delivery of relevant services such as counseling, educational training and recreation programs to bring out them from these problems and maintain the gender equality.
Keywords: Internally Displaced People; Gender equality; Gender based violence; Rehabilitation; Resettlement